Ultrasound characteristics of endometrial receptivity in patients with intrauterine adhesion following endometrial polyp surgery and their impact on pregnancy - Shen, Wenying; Yan, Lanxiang (Frontiers in Physiology, 2025)
ObjectiveThis study endeavors to investigate the ultrasound characteristics of endometrial receptivity (ER) in patients with intrauterine adhesion (IUA) following endometrial polyp surgery and their impact on pregnancy.MethodsSixty patients with IUA following endometrial polyp surgery were selected as the observation group. Another 60 healthy women undergoing physical examinations during the same period were selected as the control group. Transvaginal three-dimensional ultrasound was used to assess ER parameters, including endometrial thickness (ET), pulsatility index (PI), resistance index (RI), endometrial volume (EV), vascularization index (VI), flow index (FI), and vascularization-flow index (VFI). Patients in the observation group underwent hysteroscopic adhesiolysis and were categorized into mild, moderate, and severe adhesion subgroups based on intraoperative findings. Ultrasound parameters were compared among subgroups. After a 2-year follow-up, patients were further divided into pregnant and non-pregnant groups according to outcomes, and their ultrasound parameters were compared. Multivariate Logistic regression analysis was performed to identify factors influencing pregnancy outcomes. ROC curve analysis was used to evaluate the predictive value of ultrasound parameters for pregnancy outcomes.ResultsThe observation group had a thinner ET, smaller EV, VI, FI, and VFI, and higher PI and RI in contrast to the control group (P < 0.05). ET was thinner, EV, VI, FI, and VFI were lower, while RI and PI were higher in the moderate and severe adhesion groups compared to the mild group. These differences were more pronounced in the severe group than in the moderate group (P < 0.05). The non-pregnant group had a thinner ET, smaller EV, VI, FI, VFI, PI, and RI compared to the pregnant group (P < 0.05). Multivariate Logistic regression analysis revealed that ET, EV, PI, VI, and FI were influential factors affecting pregnancy outcomes in the observation group. ROC curve analysis demonstrated that the AUC for predicting pregnancy in the observation group were 0.796 for ET, 0.736 for EV, 0.760 for PI, 0.752 for VI, 0.652 for FI, and 0.958 for their combined assessment (P < 0.05).ConclusionER ultrasound parameters have high evaluative value in assessing patients with IUA following endometrial polyp surgery and can effectively predict pregnancy outcomes.